2003
DOI: 10.1002/jmv.10270
|View full text |Cite
|
Sign up to set email alerts
|

Difference in prognosis between patients infected with hepatitis B virus with genotype B and those with genotype C in the Okinawa Islands: A prospective study

Abstract: The factors contributing to the prognosis of hepatitis B virus (HBV)- related chronic liver disease were assessed prospectively in 72 patients with chronic hepatitis B confirmed clinically and pathologically. A comparative study was undertaken between patients infected with genotype B and those with genotype C. During the follow-up period, 13 (81.3%) of 16 patients with genotype B who were initially hepatitis B e antigen (HBeAg) positive became HBeAg negative and 14 (51.9%) of 27 with genotype C became HBeAg n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…All patients in the lamivudine-refractory, long-term treatment cohort had highly elevated levels of HBV DNA with documented lamivudine-resistance mutations at baseline, and 94% were infected with HBV genotype C. This represents a population with potentially poor long-term outcomes. Patients with lamivudine-resistant HBV may have cross-resistance to other antivirals, and genotype C infection is associated with low rates of HBe seroconversion and high rates of liver disease progression [7,25,36]. These results show that entecavir therapy for up to 3 years for this population resulted in durable HBV DNA suppression and ALT normalization.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…All patients in the lamivudine-refractory, long-term treatment cohort had highly elevated levels of HBV DNA with documented lamivudine-resistance mutations at baseline, and 94% were infected with HBV genotype C. This represents a population with potentially poor long-term outcomes. Patients with lamivudine-resistant HBV may have cross-resistance to other antivirals, and genotype C infection is associated with low rates of HBe seroconversion and high rates of liver disease progression [7,25,36]. These results show that entecavir therapy for up to 3 years for this population resulted in durable HBV DNA suppression and ALT normalization.…”
Section: Discussionmentioning
confidence: 68%
“…The relatively low rate of HBe seroconversion observed in this study (15%) may be related to infection with genotype C virus. In studies in Japan and elsewhere in Asia, HBV genotype C has been associated with lower seroconversion rates than with other HBV genotypes [7,[36][37][38]. Achieving and maintaining HBV DNA suppression is a principal goal of CHB therapy [25,39].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that HBV genotypes may influence the outcomes and the severity of HBV, mainly in Asian studies, with more serious disease observed in patients infected with genotype C (Lindh et al 1999, Kao et al 2000, Kobayashi et al 2002, Sakugawa et al 2002, Sugauchi et al 2002, Wai et al 2002, Chan et al 2003, Lee et al 2003, Nakayoshi et al 2003, Sumi et al 2003. Nevertheless, the informations about differences in the clinical, virological and histological characteristics among patients with genotypes non-B and non-C, prevailing in Western countries, are scarce and controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the information on the clinical significance of HBV genotypes has been based on studies from Asia countries and is restricted to comparisons between genotypes B and C (Lindh et al 1999, Kao et al 2002, Kobayashi et al 2002, Sakugawa et al 2002, Wai et al 2002, Lee et al 2003, Nakayoshi et al 2003, Sumi et al 2003. Few studies have evaluated the role of genotypes in non-Asian population and the infection outcomes (Mayerat et al 1999, Sanchez-Tapias et al 2002, Thakur et al 2002, Chu et al 2003, Gandhe et al 2003, Kumar et al 2005, Halfon et al 2006, Madan et al 2009).…”
mentioning
confidence: 99%
“…Reported studies found an association between HBV genotype and development of hepatocellular carcinoma, >50% of hepatocellular carcinoma patients were infected with genotype B in a Taiwan study [39].In addition, hepatocellular carcinoma in younger patients in Taiwan predominantly infected with hepatitis B virus genotype B compared to genotype C [39].In contrast, in Japan, genotype B is rarely correlated with hepatocellular carcinoma development and only in older age [40]. The disparity concerning the association of genotype B and development of hepatocellular carcinoma between Japan and Taiwan may be due differences in sub-genotype as it is B1 in Japan and B1 in Taiwan [41].…”
Section: Disccussionmentioning
confidence: 94%